Culturally Grounded Educational Leadership for Sustainable Development Goals (SDGs): A Conceptual Framework for Future Education Managers - Nilufar Djuraeva; Ra’no Khatamova; Ilyos Islamov; Nodira Xasanova; Shoira Nurullayeva; Nurjamol Maksutkanovna (ASEAN Journal of Educational Research and Technology, 2026)
This study developed a culturally grounded conceptual framework for educational leadership to support Sustainable Development Goals (SDGs). It responds to the need to prepare future education managers who can integrate strategic leadership, inclusive governance, digital capability, professional self-efficacy, and local cultural awareness. Using a conceptual research design and qualitative document analysis, the study synthesizes Central Asian historical-cultural heritage with contemporary literature on educational leadership and sustainable management. The proposed framework positions heritage as a leadership resource for strengthening institutional identity, gender-inclusive governance, and innovation-oriented educational management. The study offers a curriculum-oriented model for preparing future education managers.